(3OQGSI JMdjdjI s - (3djfOI(B, (3HNhTs ((3GdLRGFQ (B:s (3OGQ EjdjGA ddfTQ hGdJhRjY(B,s, 2024)
(3eSGQ JWhQ GdfXGe GdeUQaj GdLRGFQj aj VhA GdGUdGMGJ, JMdjd JWhQ GdfXGe GdeUQaj(B: (3HYO GdYeb GdeGdj, JMdjd JWhQ GdfXGe GdeUQaj(B: (3HYO GdhUhd (B''(3GdTehd(B''(3, GdcaGAI h GdGSJbQGQ Gdedj, h JMOjGJ EUdGM GdefXheI GdeUQajI HGdLRGFQ, JMdjd JWhQ HhQUI GdLRGFQ s
(3HHdjhYQGajG(B: (3U(B. (3U(B. 236-247s
Keywords: (3GdHhQUGJs; (3GdfXGe GdfbOj(B- (3GdLRGFQs